Dream fourteen print portfolio by Julian Simmons, Sarah Lucas - Simmons, Julian 1971-; Lucas, Sarah 1962- (Paul Stolper, 2020)
Specially commissioned and designed artist book of 14 prints by Julian Simmons and Sarah Lucas based on Lucas' Muses which she exhibited at the British Pavilion, 56th Venice International Art Biennale, Venice (2015)
Titel vom Umschlag. - "Companion publication to the print edition published by Paul Stolper 2020" (Cover hinten)
Keywords: Lucas, Sarah -- 1962-; Simmons, Julian -- 1971-; Biennale di Venezia -- 56. -- 2015 -- Venedig; Fotografie; Installation -- Kunst; Plastik; Lucas, Sarah / 1962- / Muses / Pictorial works; Simmons, Julian / 1971-; Photography of sculpture; Photography, Artistic; Pictorial works; Künstlerbuch; Bildband